Pelaksanaan Regulasi Penyiaran di Daerah, Studi Di Sepuluh Provinsi - Dian Wardiana Sjuchro (Jurnal Kajian Jurnalisme, 2017)
Democratization of broadcasting that is characterized by the diversity of ownership and diversity of content is the aspiration that stated in Law 32/2002 on Broadcasting. However, the enormous of political and business battles that follow the enactment of the broadcasting regulations have hampered its implementation in Indonesia. Now, after nearly 15 years of implementation of the Broadcasting Law in Indonesia, the time to evaluating the implementation of regulation of legislative products in the regions have arrived. Evaluations are directed more to an objective opportunities of local people to access the ownership of local television, and the impact on the content of television local to the communities. The research applied qualitative method and the data is collected by utilizing a survey to the broadcasting stakeholders in 10 areas that is determined purposively. The object of the research is local government, regional broadcasting commissions, community leaders, journalists, lecturers, and the owners of local television licensed. The results show that broadcasting regulations are relatively unworkable in the regions due to various central government policies that do not widely open the opportunities for regional people to access broadcasting licenses. This limitation also led to complaints from the region regarding the content of national television broadcasts that many harm local communities and cultures. Research respondents suggested to have more pro-regional broadcasting regulation and involving local people in the making of policies and regulations of regional broadcasting.